PENGARUH LITERASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Rianda, Rilo; Mashudi, Mashudi; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research was aimed to investigate whether literacy contribute to the Economy subject achievement of â€XI IPSâ€ students of â€MAN 1 Pontianakâ€. This was an ex post-facto research with descriptive percentage method. There were 148 â€XI IPSâ€ students who participated in this research. The sample were 60 students taken from XI IPS 1, XIÂ IPS 2, XI IPS 3 and XI IPS 4 learning class. According to the research finding, the obtained R value was 0.600 and classified as strong, since there was a positive and significant correlation between the independent variable (X) namely the studentsâ€™ literacy and the dependent variable (Y) namely the studentsâ€™ achievement. The obtaine t-value was greater than the t-table (5,705 > 2,001), indicating that the Ha was accepted and the Ho was rejected. It can be concluded that there was an contribution effect toward studentsâ€™ Economy subject achievement of Â â€XI IPSâ€ students of â€MAN 1 Pontianakâ€. Meanwhile, the determination cooeficient (R2) was 0.359 indicating the contribution effect percentage was 35.9 % . Furthermore, the rest of 64.1% was the contribution effect fromÂ several unreviewed factors in this research. Keywords: Literacy, Studentsâ€™ achievement